Oral health and behaviours of people living with Multiple Sclerosis in Australia. Issue 3 (7th January 2019) - Sexton, Christopher; Lalloo, Ratilal; Stormon, Nicole; Pateman, Kelsey; van der Mei, Ingrid; Campbell, Janet; Ford, Pauline
Abstract: Objectives: The literature describing the oral health of people with Multiple Sclerosis (MS) is scant and the findings equivocal. The aim of this study was to describe the oral health and oral self‐care behaviours of people living with MS and compare it to the Australian population. Methods: Participants enrolled with the Australian MS Longitudinal Study (AMSLS) were invited to participate in the survey using an online or paper‐based questionnaire. Data were collected on level of disability, oral health, oral self‐care and factors influencing attendance for oral health care. Results: Completed questionnaires were received for 1523 respondents. Over one‐fifth (n = 320; 22%) rated their oral health as fair or poor, and more than half (n = 840; 57%) reported toothache in the last 12 months. These proportions were higher than those for the general Australian adult population (oral health prevalence ratio (PR) = 1.25 [1.12, 1.40]; toothache PR = 3.63 [3.39, 3.88]), and this is despite comparable or better self‐maintenance habits and dental attendance reported by respondents. People with MS reported high rates of mouth dryness (68.4%), teeth sensitivity (64.7%), change of taste (40.5%) and orofacial pain (39.0%); fewer than 10% experienced none of these. There was a lower prevalence of self‐reported need for treatment (extraction or filling) than in the Australian adult population (15.8% vs 32.9%). Conclusions: People with MS have a greater oral health burden, demonstrated by their poorer self‐reported oral health than the Australian adult population. Furthermore, they experience high rates of toothache, mouth dryness, teeth sensitivity, change of taste and orofacial pain. These findings are contrary to their self‐reported good oral self‐care and dental attendance habits and suggest some of the oral health impacts are due to MS rather than dental behaviours.